Building Scalable Cloud Databases with Database Reliability Engineering - Shekhar Mishra (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the evolution and implementation of Database Reliability Engineering (DBRE) in cloud environments, focusing on the transformation from traditional database management to modern cloud-based solutions. The article examines key aspects of scalable database architectures, including elastic scalability, serverless solutions, and advanced scaling techniques. The article investigates various strategies for ensuring database reliability, performance optimization, and cost management while addressing challenges in data distribution and consistency maintenance. Through analysis of multiple cloud platforms and implementation approaches, the article demonstrates how organizations can effectively leverage automation, monitoring, and best practices to build robust, scalable database solutions that meet contemporary demands for performance and reliability.